PETROPHYSICAL APPROACH TO DETERMINATION OF KEROGEN CONTENT IN ROCKS BASED ON WELL-LOGGING DATA - Karpenko, I.; Karpenko, O.; Bashkirov, G. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The topicality of research into the physical properties of organic matter in rocks is largely associated with the prospects of a significant increase in shale gas production. Geophysical diagnostics, including assessment of kerogen content in shale-gas deposits, requires a thorough petrophysical analysis. Based on the recently published results of research into the physical properties of organic matter from the discovered US shale-gas fields, we have derived petrophysical relationships for quantitative calculations of kerogen content using well-logging data. The earlier developed system of interpretational equations contains petrophysical constants defining the individual characteristics of solid organic matter in rocks. Mathematical models have been built to relate the interval time of the longitudinal acoustic wave and specific hydrogen content to the density and catagenetic maturity of organic matter. There have been suggested equations of the identified patterns of change in the value of vitrinite reflectance with the increasing depth of the deposits for various areas of the Dnieper-Donetsk Basin. The research results also include suggestions on specifying the petrophysical characteristics of organic matter taking into account its maturity and specific oil and gas strata or areas.